Pengaruh ekspor, tingkat inflasi dan nilai tukar mata uang terhadap cadangan devisa (studi di Indonesia dan Malaysia) - Nanda Eulia; Syaparuddin Syaparuddin; Parmadi Parmadi (e-Journal Perdagangan Industri dan Moneter, 2021)
This study aims at the implications of the development of foreign exchange reserves, exports, inflation, and the exchange rate of the rupiah and Malaysian ringgit for the period 2000-2017, the implications of the effect of exports, inflation, and the rupiah exchange rate on foreign exchange reserves in Indonesia and the effect of exports, inflation and the value of the rupiah. exchange rate ringgit against Foreign Exchange Reserves in Malaysia. The type of data used in this study is secondary data which is periodic data from 2000 – 2017, hypothesis testing itself using multiple linear regression equations. The analytical tools used are the joint test (F-Test), Partial Regression Coefficient Test (t-test), and Classical Assumption Test. Based on the t-test analysis, it can be seen that exports cannot affect foreign exchange reserves. Meanwhile, inflation has a negative and significant effect on foreign exchange reserves with a coefficient of 0.159% and the exchange rate has a positive and significant effect on foreign exchange reserves with a coefficient of 1.446%. Keywords: Exports, Inflation, Exchange rates, Foreign reserves